An Empirical Study of the Acceptance of IoT-Based Smart Meter in Malaysia: The Effect of Electricity-Saving Knowledge and Environmental Awareness - Alkawsi G.A.; Ali N.; Baashar Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Energy conservation; Environmental technology; Housing; Internet of things; Smart meters; Acceptance models; Behavioural intentions; Environmental awareness; Internet of thing (IOT); Technological solution; Technology acceptance model; Unified theory of acceptance and use of technology; UTAUT2; Electric power measurement